2022
DOI: 10.1038/s41467-021-27594-w
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong single-cell profiling of cranial neural crest diversification in zebrafish

Abstract: The cranial neural crest generates a huge diversity of derivatives, including the bulk of connective and skeletal tissues of the vertebrate head. How neural crest cells acquire such extraordinary lineage potential remains unresolved. By integrating single-cell transcriptome and chromatin accessibility profiles of cranial neural crest-derived cells across the zebrafish lifetime, we observe progressive and region-specific establishment of enhancer accessibility for distinct fates. Neural crest-derived cells rapi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 52 publications
0
45
0
Order By: Relevance
“…At 14 dpf, the ucmaa-p1 enhancer, active in gill filament but not hyaline cartilage in the face, drives GFP expression in both pseudobranch and gill filament cartilage (Figure 2b), as seen for endogenous expression of ucmaa (Figure 3-figure supplement 1). In our single-cell chromatin accessibility analysis of neural crest-derived cells (Fabian et al, 2022), we also identified an irx5a proximal enhancer selectively accessible in pillar cells, a specialized type of endothelial cell in the gill secondary filaments (Figure 3-figure supplement 2). At 13, 20, 60 dpf and one-year-old adult fish, the irx5a-p1 enhancer drives GFP expression in pillar cells of the pseudobranch and gills (Figure 2c; Figure 3-figure supplement 2).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…At 14 dpf, the ucmaa-p1 enhancer, active in gill filament but not hyaline cartilage in the face, drives GFP expression in both pseudobranch and gill filament cartilage (Figure 2b), as seen for endogenous expression of ucmaa (Figure 3-figure supplement 1). In our single-cell chromatin accessibility analysis of neural crest-derived cells (Fabian et al, 2022), we also identified an irx5a proximal enhancer selectively accessible in pillar cells, a specialized type of endothelial cell in the gill secondary filaments (Figure 3-figure supplement 2). At 13, 20, 60 dpf and one-year-old adult fish, the irx5a-p1 enhancer drives GFP expression in pillar cells of the pseudobranch and gills (Figure 2c; Figure 3-figure supplement 2).…”
Section: Resultsmentioning
confidence: 82%
“…Zebrafish mutant for gata3 fails to form gill buds (Sheehan-Rooney et al, 2013), and single-cell chromatin accessibility analysis of neural crest-derived cells had implicated Gata3 and Gata2a in development of gill filament cell type differentiation (Fabian et al, 2022). We find that gata3 and gata2a are prominently expressed in both the developing pseudobranch and gill buds at 3 and 5 dpf (Figure 3a; Figure 3-figure supplement 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far gene expression during craniofacial development has been primarily studied in model organisms such as mouse, chicken, and zebrafish (Askary et al, 2017; Brugmann et al, 2010; Chang et al, 2014; ENCODE Project Consortium, 2012; Fabian et al, 2022; Hooper et al, 2017; Li et al, 2019; Potter and Potter, 2015). Due to ethical and logistical reasons, gene expression data from primary craniofacial developing human tissue are rare (Cai et al, 2005; Samuels et al, 2020) compared to the thousands of gene expression data sets produced in adult tissues by large-scale consortia such as Encode and GTEx.…”
Section: Introductionmentioning
confidence: 99%